BIODIVERSITY OF LICHENS IN THE PEAK OF MOUNT TANGKUBAN PARAHU ALONG AN ALTITUDES GRADIENT AND DISTANCE FROM THE RATU CRATER IN RELATION WITH ENVIRONMENTAL FACTORS AND GROWTH SUBSTRATE - Mustika Sari, Rima
Many lichens can be found in Mount Tangkuban Parahu, Jawa Barat. Biodiversity and distribution of lichens were influenced by microclimate factors (such as water, light, wind, temperature, and humidity), growth substrate, altitudes, and air pollution especially SO2. Microclimate factors and growth substrate were known to be closely related to altitudes. In addition, the difference of distance from Ratu crater as source of SO2 was predicted in resulting of different amount of SO2 in the air. So, change in altitudes gradient and distance from Ratu crater might reflect ecological conditions and differences in lichens communities. The aim of this research was to (1) analyze biodiversity in Mount Tangkuban Parahu along an altitudes gradient and distance from Ratu crater (2) determined quality environment of Mount Tangkuban Parahu by using IAP (Index of Atmospheric purity), (3) compared lichens biodiversity in Mount Tangkuban Parahu at years of 1990 with 2011. Research was conducted during August 2010 until March 2011. Lichens was investigated on trees with diameter stem?30 cm in 210m2 quadrant transect. Setting of quadrant was begun from area close to Ratu crater at altitude 1835m asl until the peak of Mount Tangkuban Parahu at altitude 2058 m asl. We recorded 20 species of lichens, which include 17 species of crutose lichens, one species of fruticose lichens, and two species of foliose lichens. In the area close to Ratu crater at altitudes 1835-1876 m asl, crustose lichens (Psilolechia lucida, Fulgensia fulgens, dan Lepraria incana) was found, while foliose dan fruticose lichens was absent. Foliose lichens such as Parmelia sp. was found at started altitudes ?1907 m asl, and the distance ±150m asl from Ratu crater, while fruticose lichens such as Usnea sp. can be found at altitudes ?1951 m asl, and the distance ±200m from Ratu crater. Biodiversity of lichens was shown positive correlation with the altitudes gradient and distance from Ratu crater. Comparing with Herlinda (1990), lichens biodiversity at 2011 has declined, such as foliose lichens (from 4 species to 2 species) and fruticose lichens (from 3 species to 1 species), while crustose lichens has increased (from 2 species to 17 species). Based on IAP value, peak of Mount Tangkuban Parahu was divided into two areas. First, area that was not conducive for foliose and fruticose lichens to grow (IAP as big as 2,27 and 6,57 at altitudes 1835-1945 m asl). Second, area that was conducive for growth of lichens (IAP as big as 15,09 ? IAP ? 22,73 at altitudes 1951-2050 m asl).